Nano-island-encapsulated cobalt single-atom catalysts for breaking activity-stability trade-off in Fenton-like reactions - Zhi-Quan Zhang; Pi-Jun Duan; Jie-Xuan Zheng; Yun-Qiu Xie; Chang-Wei Bai; Yi-Jiao Sun; Xin-Jia Chen; Fei Chen; Han-Qing Yu (Nature Communications)
Abstract Single-atom catalysts (SACs) have been increasingly acknowledged for their performance in sustainable Fenton-like catalysis. However, SACs face a trade-off between activity and stability in peroxymonosulfate (PMS)-based systems. Herein, we design a nano-island encapsulated single cobalt atom (CoSA/Zn.O-ZnO) catalyst to enhance the activity and stability of PMS activation for contaminant degradation via an “island-sea” synergistic effect. In this configuration, small carrier-based ZnO nanoparticles (the “islands”) are utilized to confine and stabilize Co single atoms. The expansive ZnO substrate (the “sea”) upholds a neutral microenvironment within the reaction system. The CoSA/Zn.O-ZnO/PMS system exhibits a remarkable selectivity in exclusively generating sulfate radicals (SO4 •-), leading to a complete removal of various recalcitrant pollutants within a shorter period. Characterized by minimal leaching of active sites, robust catalytic performance, and low-toxicity decontamination, this system proves highly efficient in multiple treatment cycles and complex water matrices. The design effectively breaks the activity-stability trade-off typically associated with SACs.